Learning Economic Mathematics Through the Implementation of Geogebra Learning Media: An Effectiveness Study - Yulia Pratiwi Siregar; Enni Sari Siregar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Formal education plays a crucial role in creating a high-quality workforce, and continuous innovation in the learning process is crucial, particularly through the integration of technology. This study aims to examine the effectiveness of using the GeoGebra application in improving student learning outcomes in mathematical economics, specifically regarding demand, supply, and market equilibrium functions. The method used was a quasi-experimental design with a randomized control group design. This study compared two classes: an experimental class using GeoGebra and a control class using conventional learning. The analysis showed that the use of GeoGebra was effective in improving students' conceptual understanding, particularly in the aspects of procedural fluency and graphical understanding, with a higher average score in the experimental group (88.20) compared to the control group (85.63). Although the statistical significance value (p > 0.05) did not indicate a statistically significant difference, these results still indicate that GeoGebra contributes to improved conceptual understanding. Furthermore, the analysis of the role of the moderating variable 'initial mathematical ability' explains that students' initial ability has an influence on learning outcomes but does not clearly explain the theory underlying the use of this variable. This study provides insight into the importance of using GeoGebra to improve learning outcomes in the context of mathematical economics learning at the tertiary level.